The Effects of Education on Compliance With Skin Cancer Risk Reduction Guidelines. Issue 2 (March 2015) - Chen, Connie; Woyansky, Sara; Zundell, Carrie
<x xml:space="preserve">Abstract</x> ABSTRACT The purpose of this project was to provide educational materials to healthcare professionals to enhance their ability to deliver patient-centered education and, ultimately, improve patients' comprehension of personal risk factors for developing various skin cancers. Participants were 30 future nurse practitioners selected from nursing master programs at a university in New York City. Each participant was given a knowledge-based skin cancer pretest, followed by a focused educational session regarding various types of skin cancer, methods of prevention, and methods of detection, which was heavily focused on skin cancer presentation and detection among minority populations. After the educational session, participants were given a posttest to evaluate the session and to assess their level of comfort in treating and educating patients on skin cancer awareness and protection. Ratings of the overall educational tools and their level of comfort were recorded. Overall, participants found the educational material beneficial in increasing their confidence to properly educate patients on skin cancer awareness and protection.